Blair’s Reforms and Impacts onThe Middle East - NAIT SEGHIR, Mebarka (My University, 2017)
Abstract: This research tried to shed light on the political personality of Tony Blair, The British Prime Minister for three terms, from 1997 till 2007. Britain agreed under his premiership with American policy, in particular to what was related to the Iraqi blockade of 2003 and before that Afghanistan in 2001; Blair is viewed to be the reason that led his country involved in the war in Iraq by using the pretext of fighting terrorist groups.
Keywords: of fighting terrorist groups.